Permasalahan Manajemen Usaha Mikro Studi Kasus Pada Pabrik Kerupuk UD. Manunggal Karsa Di Kel. Lebak Bulus Kec. Cilandak Kodya Jakarta Selatan - Siti Maryama (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2012)
The purpose of the study are to (1) review the main problems faced by the factory of Kepuruk Manunggal Karsa (MK), and (2) assessing the entrepreneur attempts to be able to solve the problems faced. The research was carried out using qualitative descriptive design. The results showed that (1) the lack of supply of raw materials as a result of lack of capital. Sequel is due, the difficulty of the plant to meet consumer demand (excess demand). (2), the system of capital used is circulating capital (capital turnover). Earned income used up to finance the operation of the plant. (3) Innovation has been done in the form of deal with bad weather (rain) as an effort of crackers drying process is by using the oven. (4) There has been no cooperation with financial institutions. (5) There is no organizational structure as a modern factory for traditionally managed by family management. (6) Marketing using modes of transportation carts and motor vehicles.